Kuliah Kerja Nyata Pengabdian Komunitas Maya Kepada Masyarakat Desa Karyamukti di Era Covid-19 - Taptajani, Dedi Sa'dudin; Saputra, Adi Surya; Faujan, Septian Kiki Al; Maulana, Irsan; Ramadhan, Diva Rachman; Setiawan, Dede; Yahya, Amirrudin; Suherman, Toni Hari; Mulyadi, Hadi; Saprudin, Vrisco; Nugraha, Jujun Maulana; Hakim, A. Sultoni (Jurnal PkM MIFTEK, 2022)
During the Covid-19 pandemic, many problems were faced by the community. One of the problems faced is regarding the sluggish economy in the pandemic era and online learning which is currently being driven by the government. The main problem in the economy is the lack of creativity in the community to improve their economy in the current pandemic era. Meanwhile, the main problems in online learning start from teachers who only give assignments without a clear explanation to their students, students who do not have technological devices such as smartphones, there is no internet network and students' learning motivation is lacking in dealing with this online learning. We show this Maya Community Service to increase community ideas and creativity in increasing ideas to utilize local commodities in improving the economy, then trying to increase teacher capacity in processing learning materials and increasing student collaboration in dealing with online learning. The methodology used is the Integration methodology for KKN participants, where the implementation method uses a combination method, but online activities dominate due to situations that make it impossible to carry out offline related to health protocols. The results achieved are by increasing the ideas and creativity of the community in processing local commodities they can improve the economy in Karyamukti village and by increasing the ability of teachers to process online learning materials and students can access and understand material in carrying out online learning processes.